2021
DOI: 10.3390/plants10102102
|View full text |Cite
|
Sign up to set email alerts
|

A New Sesquiterpene Essential Oil from the Native Andean Species Jungia rugosa Less (Asteraceae): Chemical Analysis, Enantiomeric Evaluation, and Cholinergic Activity

Abstract: As part of a project devoted to the phytochemical study of Ecuadorian biodiversity, new essential oils are systematically distilled and analysed. In the present work, Jungia rugosa Less (Asteraceae) has been selected and some wild specimens collected to investigate the volatile fraction. The essential oil, obtained from fresh leaves, was analysed for the first time in the present study. The chemical composition was determined by gas chromatography, coupled to mass spectrometry (GC-MS) for qualitative analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
4
0
2
Order By: Relevance
“…Calvopiña et al [ 8 ] studied the chemical analysis of a new sesquiterpene essential oil from the native Andean species Jungia rugosa and studied its cholinergic activity. The results showed that the volatile fraction of this EO was exclusively composed of sesquiterpenes, specially curcumene (more than 45%) and sesquiphellandrene (about 17%).…”
Section: Antimicrobial Phytotoxic Activity and Agri-food Applicationsmentioning
confidence: 99%
“…Calvopiña et al [ 8 ] studied the chemical analysis of a new sesquiterpene essential oil from the native Andean species Jungia rugosa and studied its cholinergic activity. The results showed that the volatile fraction of this EO was exclusively composed of sesquiterpenes, specially curcumene (more than 45%) and sesquiphellandrene (about 17%).…”
Section: Antimicrobial Phytotoxic Activity and Agri-food Applicationsmentioning
confidence: 99%
“…For this reason, our group has been investigating the phytochemistry of the Ecuadorian flora for more than 20 years, by describing the major metabolites of unprecedented botanical species [ 4 , 5 , 6 , 7 , 8 , 9 ]. Together with nonvolatile compounds, we are very interested in essential oils (EOs), defined by the European Pharmacopoeia as “odorous products, usually of complex composition, obtained from a botanically defined plant raw material by steam distillation, dry distillation, or a suitable mechanical process without heating” [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Our interest in the EOs derives from the commercial importance of these mixtures and, overall, from the fact that they can be sources of new or rare sesquiterpenoids, often biologically active, together with enantiomeric compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils (EOs) are defined by the European Pharmacopoeia as “odorous products, usually of complex composition, obtained from a botanically defined plant raw material by steam-distillation, dry distillation, or a suitable mechanical process without heating” [ 1 ]. Since these products present a wide range of applications and biological activities, together with a great commercial interest, our group is currently engaged in the study of volatile fractions from plants [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. In particular, we are interested in EOs characterized by the presence of abundant sesquiterpene fractions, possibly dominated by new or rare sesquiterpenes.…”
Section: Introductionmentioning
confidence: 99%